Rheological Behavior of Water Soluble Glycolipids: A Comparison of Octyl-Î²-D-Glucopyranoside and Dodecyl-Î²-D-maltoside Emulsion System - Misran, Misni; Cok King, Tan; Boris Bhola, Niraula; Ahmad, Noraini (Malaysian Journal of Science, 2003)
Surfactant stabilized oil-in-water emulsions are widely used in the formulation of pharmaceutical and cosmetic products. Flow behaviors of maltose ether and glucose ether stabilized emulsions were explored in this work with the help of two types of rheology experiments, namely: steady shear and oscillatory shear experiment. A shear rate controlled Bohlin made VOR rheometer was used for this purpose. At low shear rate domain, a shear thinning non-Newtonian flow behavior characterized by an exponential decay of the Î· was observed in both cases. On the contrary, at high shear rate domain, a close to shear rate independent flow behaviors (close to Newtonian flow behavior) was observed. The degree of shear thinning depended on the surfactant type, with DDM stabilized emulsions showing a higher rate of shear thinning compared to OGP stabilized emulsions. The shear thinning property was coupled with Bingham plastic property, with all emulsions investigated in this work show a reasonably high value of $σ_y$. Much like shear thinning property, $σ_y$ depended on both the surfactant type and concentration, with DDM (56 Pa) stabilized emulsions showing higher value of yield stress compared to OGP (15 Pa) stabilized emulsions. $σ_y$ increased with surfactant concentration. These properties indicated DDM stabilized emulsion produced better quality emulsion with better storage stability and shelf life. Viscoelastic properties were measured with the help of oscillation test. Oscillation measurement were performed within the linear visco-elastic region, which in turn suggested that DDM stabilized emulsions displayed higher value of both the G' and G" responses compared to OGP stabilized emulsions over all frequencies domain measured in this work. The fact that G" response of both samples is dominant over G' throughout the entire frequency domain indicated that viscous property is dominant over elastic property. The fact that G' of DDM stabilized emulsion was higher than OGP stabilized emulsions suggested that DDM stabilized emulsions are more easily spread with higher storage stability and extensive shelf life compared to OGP stabilized emulsions. Phase angle, which is an indictor of degree of elastic and viscous properties, was higher than 40Â° through out all measured frequency domain, implying that viscous property dominated elastic property in both cases. Interestingly, phase angle could be reduced with increasing surfactant concentration suggesting that elastic property of these emulsions can be enhanced over viscous property by increasing surfactant concentration. Unfortunately, plot of G" response against G' did not yield a Cole-Cole plot with semi-circle shape, implying that, though these materials showed viscoelastic property, flow behaviors of these emulsions can be described by simple Maxwell type fluid flow model. Further, though these emulsions seemed relatively stable and that no imminent phase separation was observed, some change such as increase in droplet sizes and shapes were observed after the storage-time of two months due probably to Ostwald ripening process. Similarly, both the shape and size of emulsion droplets changed under the influence of applied shear.